Pengaruh Kualitas Produk dan Citra Merek terhadap Proses Keputusan Pembelian pada PD Marmara Garut - Wati Susilawati (Jurnal Wacana Ekonomi, 2016)
The purpose of this study was to determine the effect of product quality and brand image on purchasing decisions at PD. MARMARA Garut. The hypothesis used in this study is that there is an effect of product quality and brand image on purchasing decisions at PD.MARMARA Garut. This research uses descriptive method, with a total sample of 50 respondents. The analysis technique used in this study is multiple linear regression analysis using SPSS From window 20.0. The partial test results show that the quality of the product has an effect on purchasing decisions and the brand image has an effect on the purchase decision. Further testing simultaneously shows that the product quality and brand image have an effect on the purchasing decision process in PD MARMARA Garut.